Analysis Of Novel Curve Microstripline Array Antenna Design In X Band Frequency For Satellite Communication - Putu Artawan (Green Publisher Indonesia, 2022)
The design of a novel curve microstripline 2x2 array antenna is presented in this research. In this design, antenna work in X Band frequency. The total size of antenna is 40mm x 40mm. The result indicates that the antenna characteristics parametric showed by Voltage Standing Wave Ratio (VSWR≤2) of the proposed antenna is 1.06 (in simulated); 1.29 (in measured) and 1.20 (in numeric analyzed), bandwidth is 260.0 MHz (in simulated) and 310.0 MHz (in measured) and reflection coefficient is 0.03 (in simulated) and 0.17 (in measured) and return loss is -29.43dB (in simulated) and -27.12dB (in measured) respectively. The antenna has achieved a stable radiation performance with a maximum gain of 6.67dB (in simulated) and 5.53dB (in mesured). Novel curve microstripline 2x2 array antenna with 50 Ohm impedance and easy integration are making this model suitable for X-Band frequency (8GHz-12GHz) satellite communication applications. Details of the proposed antenna design and results are presented and discussed.